Case Report: Identification of Compound Heterozygous Mutations in a Patient With Late-Onset Glycogen Storage Disease Type II (Pompe Disease) - Huiting Zhang; Jun Chen; Yuchang Zhu; Xiaotang Ma; Wangtao Zhong (Frontiers in Neurology, 2022)
Pompe disease is an autosomal recessive hereditary lysosomal disorder and correlated with acid α-glucosidase enzyme (GAA) deficiencies, which lead to accumulation of glycogen in all tissues, most notably in skeletal muscles. Adult late-onset Pompe disease (LOPD) is a slowly progressive disease of proximal myopathy with later involvement of the respiratory muscles, resulting in respiratory failure. In this study, we reported a 22-year-old Chinese woman with inability to withstand heavy physical activity since childhood, who presented with respiratory and ambulation weakness in 2 months. On admission, her bilateral upper limbs strength was 4/5 and lower limbs strength was 3/5 according to Medical Research Council (MRC) score. The patient had compound heterozygotes containing a newly identified 4 nt deletion of coding sequence (deletion nt 1411_1414) in one of the acid α-glucosidase alleles and a c.2238G>C (p.Trp746Cys) missense mutation. This deletion has been reported in infant-onset Pompe disease (IOPD) but not LOPD. Intriguingly, this deletion mutation was not found in the patient's family and was considered as pathogenic. Muscle biopsy showed scattered vacuoles with basophilic granules inside the subsarcolemmal area, which were strongly stained by periodic acid-Schiff (PAS). Laboratory tests revealed a significant increase of creatine kinase MB isoenzyme (CK-MB) and lactate dehydrogenase (LDH). GAA level was 9.77 nmol/1 h/mg and was not sufficient for the diagnosis of GAA activity deficiency (0–3.78 nmol/1 h/mg). In summary, mutational analysis of GAA and muscle biopsy are crucial in the diagnosis of Pompe disease.